Demand for household sanitation: The case of India - Anurag Banerjee; Nilanjan Banik; Ashvika Dalmia (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2016)
Worldwide, India has the highest number of people defecating in the open. In an attempt to reduce number of open defecation, a supply side initiative is underway. In 2014-2015, Government of India, constructed 8 million toilets. However, an important aspect for this supply-side initiative to become successful is to create demand for toilets. In this paper we look at household demand for toilets, and study the factors leading to open defecation. Using Demographic and Health Survey data we create a wealth index, and use it to rank household preference for toilets vis-à-vis 20 other different consumer durables. Our results suggest, among lists of household items that any individual want to have, toilets get a lower preference - ranked 12, out of 21. Additionally, we examine preference structure for using toilets among residents from various federal states in India. We find residents of North-Eastern states are more likely to use toilets. We further investigate factors leading to toilet usage among households. Results indicate a strong case for imparting education and public awareness, especially, among the female cohort.
Keywords: C01; I18; O11; 330; India; Sanitation; Toilets; Preference Structure; Logit; NFHS-3